آراء معلمي و مديري مدارس التعليم العام الحكومية بدولة الكويت حول دمج ذوي صوبات التعلم في مدارس العاديين - إشكناني، أحمد غلوم (جامعة الإسكندرية - كلية رياض الأطفال, 2011)
استهدفت الدراسة تعرف أهم آراء المعلمين ومديري مدارس التعليم العام حول دمج ذوي صعوبات التعلم في مدارس العاديين بدولة الكويت، مع بيان أهم متطلبات الدمج، ورصد أهم معوقات دمج ذوي صعوبات التعلم في مدارس العاديين بدولة الكويت، فضلا عن التحقق من مدى وجود فروق ذات دلالة إحصائية بين آراء أفراد العينة حول دمج ذوي صعوبات التعلم في مدارس العاديين بدولة الكويت ومتطلبات ومعوقات ذلك، تبعا للمتغيرات (النوع- المؤهل العلمي- الوظيفة الحالية- المرحلة التعليمية- عدد سنوات الخبرة في المجال التربوي). وقد تم اختيار عينة قدرها (150) فردا من معلمي ومديري بعض مدارس التعليم العام بالمراحل المختلفة التي تم فيها تجربة الدمج في العام الدراسي 2009/2010، وقد تم تجميع آراؤهم من خلال استبانة صممت خصيصا لهذا الغرض، وقد أشارت نتائج الدراسة إلى أن حوالي (75%) من أفراد العينة أفادوا بتلقيهم تدريبا مسبقا للتعامل مع ذوي صعوبات التعلم، وأن حوالي (68%) أفادوا بأنهم سبق قيامهم بالتدريس للطلبة ذوي صعوبات التعلم، وفيما يتعلق بآراء المعلمين ومديري المدارس حول دمج ذوي صعوبات التعلم في مدارس العاديين، تبين أنه قد اختلفت الآراء وتعددت حول فلسفة الدمج، وإن كانت غالبية الآراء تتجه نحو الموافقة على دمج ذوي صعوبات التعلم في مدارس العاديين. وقد أجمع المعلمون ومديرو المدارس على ضرورة توافر المجموعة من المتطلبات لنجاح عملية الدمج، كما أفاد أفراد العينة بأن هناك مجموعة من المعوقات تحول دون نجاح عملية الدمج، ومن أهم تلك المعوقات هي: قلة خبرة المعلمين في أساليب التعامل مع ذوي صعوبات التعلم، والافتقار إلى البرامج والأنشطة المناسبة لتفاعل الطلبة من ذوي صعوبات التعلم مع أقرانهم العاديين، وعدم وجود المعلمين المؤهلين للتعامل مع الطلبة ذوي صعوبات التعلم، كذلك عدم مناسبة أساليب تقويم الطلبة الحالية للطلبة من ذوي صعوبات التعلم. وقد تبين أنه لا توجد فروق ذات دلالة إحصائية تعزى لمتغير النوع في الآراء حول الدمج، ومعوقات الدمج، بينما وجد هناك فروق ذات دلالة إحصائية حول متطلبات الدمج لصالح مجموعة الإناث، وقد تبين أنه لا توجد فروق ذات دلالة إحصائية في الآراء حول الدمج، ومتطلبات الدمج، ومعوقات الدمج، تعزى للمتغيرات النوع، أو المؤهل العلمي، أو عدد سنوات الخبرة، أو المرحلة التعليمية التي يعملون بها؛ وهذا يعطي دلالة على أن جميع المعلمين على اختلاف النوع أو على اختلاف مؤهلاتهم الدراسية، أو عدد سنوات الخبرة، أو المنطقة التعليمية التي يعملون بها لديهم اتجاهات إيجابية نحو الدمج، كذلك يتفقون على ضرورة توافر مجموعة من المتطلبات لنجاح عملية الدمج، وكذلك وجود مجموعة من المعوقات التي يرون ضرورة مواجهتها لتحقيق الأهداف المرجوة من عملية الدمج This study aimed at the identification of the teachers, and principals vital view on the merger of students of learning difficulties with regular students at the public schools in Kuwait, with a highlight of the necessary requirements for the merger, and monitoring imperative obstacles which may be preventing the integration of students with learning difficulties in regular schools, as well as verification of the existence of statistically significant differences between the views of respondents about the process of reintegration requirements and constraints of that, depending on the variables (Type - Qualifications - Current Position - educational level - the number of years of experience in the field of education). \ A sample of (150) members has been selected of teachers and principals of some public schools from different grades in which the merger was experienced during the academic year 2009/2010. \ Their opinions have been assembled through a questionnaire designed specifically for this purpose. The study results indicated that about (75%) of respondents reported having received training in advance to deal with people with learning difficulties. And about (68%) reported that they were already had experienced teaching students with learning difficulties. \ In regard to the views of teachers and principals on the merger of students with learning difficulties in' regular schools, it was found that there was different views and numerous on the philosophy of merger, although the majority views tend towards approving the merger. \ Teachers and principals called for the need to the create a set of requirements to insure the success of any potential merger, as reported by the respondents that there is a range of obstacles preventing the success of the merger, and the most important of these obstacles were: lack of experience of teachers in methods of dealing with student with learning difficulties, and lack of appropriate programs and activities for the interaction of students with learning difficulties with their normal peers, and the lack of qualified teachers to deal with students with learning disabilities, as well as the lack of appropriate methods of evaluating the current students with learning difficulties. \ It was found that there was no statistically significant differences due to the variable type in the view's on the merger, and constraints of the merger, while it was found there were significant differences on the requirements of merger in favor of the female, has been shown that there was no statistically significant differences in views on the merger, and the requirements of integration . and constraints of the merger, due to variables: qualification, or the number of years of experience, or level of education which they operate; and this gives an indication that all teachers of different type or different academic qualifications, or the number of years of experience, or the school district in which they operate have positive attitudes towards integration, as well as agree on the need for a set of requirements for the success of the merger, as well as a set of constraints that they see the need to be met to achieve the desired objectives of the merger.
671316
Keywords: النظم التعليمية -- تعليم ذوي الاحتياجات الخاصة -- صعوبات التعلم -- دمج الطلاب -- الكويت -- مهارات القراءة -- الاضرابات النفسية -- طلاب المدارس -- المدارس الحكومية